SOCIOPRAGMATIC PECULIARITIES OF «INFODEMIC» IN ARABIC SOCIAL MEDIA DISCOURSE - KUCHERENKO, Alina (Linguistic and Conceptual Worldviews, 2022)
The term «infodemic» is nowadays used by the WHO to describe the excessive flows of inaccurate and unreliable data about the coronavirus both in the virtual and real worlds. This phenomenon is reflected in the social media posts containing the misleading information that involves fake news, rumours, nonchecked «facts», users’ thoughts, emotional reactions to different events, other online posts or messages. The previous researches include the creation of various Arabic Covid-19 misinformation datasets. However, a more in-depth analysis of the online discourse is needed due to the lack of its linguistic, so- ciolinguistic and communicative studies. This paper deals with the sociopragmatic aspect of the online communication in the Arab world during the Covid-19 pandemic. The communicants’ social features are presented within their Facebook and Twitter accounts. We manually collected nearly 100 online posts on Facebook and Twitter. We analysed the users’ communicative goals, and, especially, the linguistic tools utilized to achieve those goals, as well as the language variation caused by different communicative purposes of the «info- demic» posts. The key words of the data research are represented with the pandemic related lexemes of Twitter hashtags, such as kuruna «corona», liqah «vaccine», dawa’ «remedy», etc. We classified the studied publications according to the following topics: pharmaceutical companies’ profits; denial of the role of vaccination and the preventive measures; persuasion of the effective drugs existence; health tips. As speech acts, the studied posts involve such types as representatives (fake news, pseudofacts, etc.), directives (health advises), and expressives (attitudes, emotions, thoughts, etc.). On the other hand, the given texts are regarded as the acts of disagreement (explicit or implicit). The explicit means of negation is represented with the grammatical particles, meanwhile the implicit instruments include the lexis with the negative emotional expressivity or negative connotations. It was also noticed, that some male texts use the negative lexicon more frequently, than the female ones. The language variation reveals the relation between the post’s communicative purpose and the code choice (MSA is preferred for the representative posts (to demonstrate the credibility), ESA (Educated Spoken Arabic) is used in all types of «infodemic» posts, Colloquial Arabic as the language of everyday communication is mostly present in the expressives).